Cápsulas de tipranavir: validação de método indicativo de estabilidade por eletroforese capilar de zona e identificação de produtos de oxidação - Lago, Matheus Wagner (2017)
Tipranavir (TPV) is one of the newest drugs of the protease inhibitors class, which is indicated to patients with human immunodeficiency virus, who present therapeutic failure to other antiretrovirals of this class. It is available as a 250 mg capsule and 100 mg.mL-1 oral solution. Although commercially available since 2005, are not yet available in pharmacopoeias analytical methods for drug analysis in raw materials and formulations, as well as studies on its stability. The objective of this study was to develop and validate a quantitative capillary zone electrophoresis method for the analysis of TPV in capsules and to identify possible degradation products obtained by forced degradation studies. The reference substance was characterized by infrared spectrophotometry, ultraviolet spectrophotometry and high resolution mass spectrometry. Additionally, an impurity evidenced in the active pharmaceutical ingredient was identified by high resolution mass spectrometry and consisted of a product related to the oxidation of the TPV. The method developed met the current requirements, presenting linearity in the range of 20 to 200 μg mL-1, accuracy (recovery percentage of 100.50% ± 1.57%, n = 9), precision (interday RSD = 1.59%, n = 12), and specificity, which was evidenced by the peak purity in forced degradation studies. Robustness was assessed by 23 factorial design factorial and the results indicated that the method is robust even with small modifications in voltage, temperature and buffer concentration. By the forced degradation study, it was evidenced that the oxidation is the faster route of TPV degradation. Thus, the kinetics of degradation in oxidizing medium was determined, and the major degradation product in that condition was identified. In view of the results, care in the choice of excipients and packages is relevant to avoid oxidation of the drug.